Sex-dependent dominance at a single locus maintains variation in age at maturity in salmon - Barson, Nicola J.; Aykanat, Tutku; Hindar, Kjetil; Baranski, Matthew; Bolstad, Geir H.; Fiske, Peder; Jacq, Céleste; Jensen, Arne J.; Johnston, Susan E.; Karlsson, Sten; Kent, Matthew; Moen, Thomas; et al.
2015